APLIKASI MANAJEMEN INVENTARIS BERBASIS MOBILE PADA CV LAFEBY MENGGUNAKAN METODE AGILE - Prasetyo, Stefanus Eko; Aripradono, Heru Wijayanto; Candra, Boby (LPPM UNIVERSITAS BINA INSAN, 2023)
The utilization of technology at this time increasingly encourages businesses or industries to build an efficient work ecosystem. Inventory management is one of the important keys in the company's ecosystem. Inventory management is a process of managing and monitoring raw or finished goods. CV Lafeby is a medium-sized business engaged in textiles. Currently CV Lafeby still uses a conventional system in managing its inventory management such as recording incoming products using paper or making paper notes. The use of conventional systems has many problems such as the absence of up to date product data and the use of paper notes is too risky to be damaged or lost. The impact of incomplete data on incoming goods and outgoing goods will affect CV Lafeby in the future. Therefore, CV Lafeby needs an inventory management system by utilizing technology, namely a mobile application and mysql database. The author uses the agile development method in developing mobile applications. Later, the backend of the mobile application will be built through hosting so that the data can be obtained up to date. Hopefully, the mobile application that the author will develop can solve the problems of the shortcomings caused by conventional systems in inventory management.